Why do firms in weak institutional environments adopt strong corporate governance? The role of government regulation - Zhang, Xiaojun (2015)
This study identifies one potential benefit of mandatory investor protection laws in weak investor protection countries neglected by the extant literature: laws help reduce firms’ bonding costs to strong corporate governance. We argue that corporate insiders (outsiders) have little incentive to voluntarily supply (demand) strong corporate governance in weak legal regimes because such voluntary bonding is not a credible commitment. However, once some corporate governance provisionsare mandated by law, they can serve as a more credible bonding mechanism at lower costs. Hence, many firms that expect to benefit from such bonding should comply with the corporate governance provisions in the mandatory regime. Using several different corporate governance proxies, we find supporting evidence for our conjectures. In addition, we find some evidence that firms that adopt strong corporate governance in the mandatory corporate governance regime are rewarded with a higher earnings response coefficient.